SUNAT: Torpedeando a la Marina Mercante Nacional - Villanueva González, Martín (2014)
In this article, the author describes the problems that come through the Peruvian shipping companies because of misinterpretations made by the tax authority about the scope of the Law for reactivation and promotion of the National Merchant Marine; to harmful tax collection procedures and poor debt settlement system controversies between taxpayers and the Tax Administration.